The Philosophy for Children School and the inequalities in New Zealand's school achievement : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University, Manawatū, New Zealand - Comer, Bridget Anne (Massey University, 2015)
The New Zealand educational system has faced major reformation in the last 20 years resulting in an inequality of achievement, also known as the long tail of underachievement. New Zealand’s results in the Programme for International Student Assessment (PISA) has steadily declined since the assessments beginning; which is similar to other countries who have initiated high stakes, standardised based testing policies. If New Zealand is to address the declining results and attempt to alleviate the gap between its highest and lowest achievers, and address educational inequalities, then alternative approaches must be considered. This thesis outlines the Philosophy for Children (P4C) School as a viable within-school approach to addressing educational inequalities through the implementation of the principles underlying the Community of Inquiry (COI), the Philosophy for Children Programme and democratic education as a whole school approach.
Keywords: Academic achievement; Educational equalization; Children and philosophy; New Zealand